Pembelajaran TPACK untuk Keterampilan Komunikasi dan Hasil Belajar Siswa pada Jaringan Komunikasi - Perdana, Novi Theofilia; Koriaty, Sri; Oktarika, Dini (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
The aim of this research is to analyze the effect of TPACK-oriented learning on students' communication skills and student learning outcomes in communication network subjects. This research uses a quasi-experimental method with a pretest posttest kontrol group design. Research instruments include observation guides, interview guides, tests and questionnaires. in this research used a quantitative method. This research method aims to test a predetermined hypothesis which will be used to research certain populations and samples, collect data using research instruments, and analyze quantitative or statistical data. The type of method used is quantitative in the form of quasi-experimental design. The research design used was a pretest-posttest kontrol group design. The results of this research after implementing the TPACK learning model showed a significant increase in the acquisition of learning outcome data in the kontrol class, namely the average value of learning outcomes in the pre-test was 55.22 and the average value of learning outcomes in the post-test increased by 61.14. Meanwhile, for the experimental class, the average value of learning outcomes in the pre-test was 56.08 and the average value of learning outcomes in the post-test increased by 81.06.